Construire les Carpates: L'Institutionnalisation d'une Éco-Region - Gaberell, Simon (Peter Lang International Academic Publishers, 2015)
This book promotes a new understanding of the regional monograph. It investigates its research topic - the Carpathian Mountains - through the prism of institutions and organizations that have objectified it and have interacted in its governance over the past ten years. As such, the Carpathian Mountains never constitute an object per se in this book, but are rather understood as a region continuously objectified by discourses, inscriptions and practices. Four months of ethnographic field work under the direction of the United Nations Environment Programme (UNEP) at the interim secretariat of the Carpathian Convention have unveiled environmental institutions that remain largely unknown to both the general public and to researchers.